Grant Wood American Gothic and other fables - Wood, Grant 1891-1942; Haskell, Barbara 1946-; Adamson, Glenn 1972-; Banks, Eric 1966-; Braun, Emily 1957-; Meyer, Richard 1952-; Reece-Hughes, Shirley (Whitney Museum of American Art, 2018)
The social and political climate in which Wood's art flourished bears certain striking similarities to America today, as national identity and the tension between urban and rural areas reemerge as polarizing issues in a country facing the consequences of globalization and the technological revolution. Wood portrayed the tension and alienation of contemporary experience. By fusing meticulously observed reality with fables of childhood, he crafted unsettling images of estrangement and apprehension that pictorially manifest the anxiety of modern life
Catalogue published on the occasion of the exhibition Grant Wood: American Gothic and Other Fables, organized by Barbara Haskell, curator; Whitney Museum of American Art, New York, March 2-June 10, 2018. - Includes bibliographical references and index
Keywords: Wood, Grant -- 1891-1942 -- Exhibitions; Wood, Grant -- 1891-1942; Ausstellungskatalog -- Whitney Museum of American Art -- 02.03.2018-10.06.2018 -- New York, NY